Digital Storytelling Resources for Critical Listening: A CEFR-Based Approach for Middle Schoolers - Fitri Jayanti; Lala Bumela Sudimantara (Journal of English Language Teaching and Cultural Studies, 2023)
CEFR has become a crucial framework for language curricula design and learning outcomes assessment worldwide. In Indonesia, critical listening has emerged as a significant student skill to learn, yet middle schools face challenges in mastering it. Sudimantara (2021) has integrated innovative listening activities using filtered intonation in Verbotonal Approach to enhance English academic writing skills. The holistic pedagogy integrates listening, speaking, reading, and writing, incorporating multisensory load reduction strategies and innovative learning tools such as Reading for Emotion and Aesthetics. Sudimantara's approach breaks away from pedagogic grammar and improves learning outcomes. The research aims to enhance students' listening skills and improve the CEFR-based digital storytelling resources as a pedagogical practice. The qualitative data with research and development (R&D) design findings that the creative processes involved analyzing lesson plans, which the researchers found to still rely on traditional teaching methods, utilizing the Reading for Emotions approach as a learning tool to analyze texts and analyzing texts based on the CEFR level using a virtual writing tutor website. In this research, the characterization results of the creative processes are the creation of a product prototype, namely digital storytelling resources for critical listening based on CEFR. The study utilized a curriculum engineering approach that prioritized student-centeredness and differentiated learning over an uninformative approach based on rhizomatics, which focuses on endless learning.